(untitled) (Global Journal of Science Frontier Research, 2024)
Scientific research organizations have a long-standing tradition in NATO s history testifying to the great role that Alliance decision-makers attach to scientific research Thanks to comprehensive scientific development the existence of specialized scientific institutions and cooperation with research units of member states it was and is possible to develop and grow NATO s power Thanks to scientists the Alliance has for many years been a world leader in the development and application of modern military technology The assembly and cooperation of leading representatives of the scientific and technological world of the member countries has made it possible to develop and implement many innovations in the field of defence With the passage of years it has become necessary to develop specialized scientific and research institutions conducting new research and addressing further challenges facing the defence policy of the Alliance NATO s first scientific research organization was AGARD dedicated to aerospace research and the development of scientific cooperation The goal of the DRG established in 1967 was to promote technical cooperation among allied countries in research and new technologies leading to the development of defence equipment From the merger of AGARD and DRG the RTO was formed operating in the field of defence research and technology Since 2012 STO has been operating to meet the scientific and technological needs of the Alliance